Stable isotopes in monsoon precipitation and water vapour in Nagqu, Tibet, and their implications for monsoon moisture - He, Siyuan; Richards, Keith (Journal of hydrology (Amsterdam), 2016)
•Stable isotope signals change rapidly between the pre-monsoon and monsoon seasons.•Moisture sources vary through mixing of advected moisture with local recycling.•Both “temperature effect” and “amount effect” occurs in the transition zones.•High frequency stable isotopic data show “amount effect” in night-time rainfall. Understanding climate variations over the Qinghai-Tibetan plateau has become essential because the high plateau sustains various ecosystems and water sources, and impacts on the Asian monsoon system. This paper provides new information from isotopic signals in meteoric water and atmospheric water vapour on the Qinghai-Tibetan Plateau using high frequency observation data over a relatively short period. The aim is to explore temporal moisture changes and annual variations at the onset and during the summer monsoon season at a transitional site with respect to the monsoon influence. Data show that high frequency and short period observations can reveal typical moisture changes from the pre-monsoon to the monsoon seasons (2010), and the large variation in isotopic signals in different years with respect to active/inactive periods during a mature phase of the monsoon (2011), especially inferring from the temporal changes in the d-excess of precipitation and its relationship with δ18O values, when higher d-excess is found in the pre-monsoon precipitation. In this transition zone on a daily basis, δ18O values in precipitation are controlled mainly by the amount of rainfall during the monsoon season, while temperature seems more important before the onset of monsoon. Furthermore, the “amount effect” is significant for night-time rain events. From comparison of signals in both the precipitation and water vapour, an inconsistent relationship between d-excess values suggests various moisture fluxes are active in a short period. The temporal pattern of isotopic signal change from the onset of the monsoon to the mature monsoon phase provides information about the larger circulation dynamics of the Asian monsoon.